The role of coexisting cardiovascular disease on disease severity in patients with inflammatory bowel disease. Issue 5 (May 2020) - Mantaka, Aikaterini; Tsoukali, Emmanouela; Fragkaki, Maria; Karmiris, Konstantinos; Viazis, Nikos; Mantzaris, Gerassimos J.; Koutroubakis, Ioannis E.
Abstract : Objectives: Chronic inflammation has been implicated in the pathogenesis of atherosclerosis and cardiovascular disease. Data linking the severity of inflammatory bowel disease to coexisting cardiovascular disease are scarce. The aim of the present study was to investigate whether inflammatory bowel disease patients with coexistent cardiovascular disease have more severe disease. Methods: We included 103 inflammatory bowel disease patients with coexisting cardiovascular disease compared to 206 age- and sex-matched inflammatory bowel disease patients without cardiovascular disease derived from three referral inflammatory bowel disease Centers. Traditional cardiovascular disease factors and parameters of inflammatory bowel disease severity were compared between the two groups. Results: Cardiovascular disease was diagnosed after the inflammatory bowel disease diagnosis in 56.6% of cases. No significant difference was found in the prevalence of surrogate markers of severity (inflammatory bowel disease-related surgeries, hospitalizations, biologics or immunosuppressants' use, and persistent CRP elevation) between inflammatory bowel disease patients with and without cardiovascular disease. There was no difference between cardiovascular disease patients diagnosed before and after inflammatory bowel disease onset. All traditional risk factors (hypertension, dyslipidemia, smoking, obesity, diabetes mellitus) were significantly more common in cardiovascular disease patients. Cardiovascular disease patients had a trend for lower rates of multiple hospitalizations (16.5% vs. 24.3%, P = 0.05) and inflammatory bowel disease-related surgeries ( P = 0.09). Conclusion: The inflammatory burden possibly plays a less important role in the development of cardiovascular disease in inflammatory bowel disease patients but future larger prospective studies are needed.